2012
DOI: 10.1177/0013916512469099
|View full text |Cite
|
Sign up to set email alerts
|

Motivating Sustainable Food Choices

Abstract: Small, everyday changes in people's behavior can have significant positive environmental impacts. To this end, the research reported here focused on the role of an asymmetric intervention (a "nudge") in motivating choices with positive environmental outcomes. The context of this research was motivating proenvironmental food choice in campus dining halls. An experiment was conducted in which a default menu, presenting only appealing or unappealing meat-free meal options, was compared with more conventional menu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
58
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 185 publications
(65 citation statements)
references
References 58 publications
7
58
0
Order By: Relevance
“…Therefore, given that poverty-related charities are perceived more favorably than environmental charities (Forbes, 2013), a tentative explanation is that participants' awareness of this imbalance may have weakened a perceived relation between the default option and social norms. This explanation fits with work suggesting that the attractiveness of the options moderates default effects (Campbell-Arvai et al, 2012), such that default effects is more pronounced for attractive options. Of course, future research is needed to test this hypothesis more fully with regard to social norms.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Therefore, given that poverty-related charities are perceived more favorably than environmental charities (Forbes, 2013), a tentative explanation is that participants' awareness of this imbalance may have weakened a perceived relation between the default option and social norms. This explanation fits with work suggesting that the attractiveness of the options moderates default effects (Campbell-Arvai et al, 2012), such that default effects is more pronounced for attractive options. Of course, future research is needed to test this hypothesis more fully with regard to social norms.…”
Section: Discussionsupporting
confidence: 85%
“…In this study, rather than a non-specified charity that focused primarily on helping people in the developing world, we had participants choose to donate their bonus money to a specific environmental charity-Greenpeace. Previous work has suggested that default effects could be moderated by the attractiveness of the options (Campbell-Arvai et al, 2012), and it is known that people donate substantially more to povertyrelated charities than environmental ones (Forbes, 2013), suggesting that such charities are seen as being more appropriate receivers of donations. Given that individuals are generally more inclined to donate to anti-poverty charities and other charities that primarily benefit other people, we aimed to explore whether default effects would also be observed for a "higher threshold" environmental charity.…”
Section: Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with Campbell-Arvai, Arvai, and Kalof's (2014) finding, providing information about negative environmental consequences of specific food items does not influence the choice of environmentally friendly menu options. Providing such information may be helpful to educate consumers about the environmental impact of food consumption, but it is not effective in encouraging behavioural change (Campbell-Arvai et al, 2014). Our findings confirm that communication of environmental information does not necessarily make the issue of sustainability relevant to decision-making (Font & McCabe, 2017).…”
Section: Discussionsupporting
confidence: 65%
“…If this is not the case, the insights relating to acceptance and appreciation of the message contained in the label are meaningless (Wedel & Pieters, 2008). Consistent with Campbell-Arvai, Arvai, and Kalof's (2014) finding, providing information about negative environmental consequences of specific food items does not influence the choice of environmentally friendly menu options. Providing such information may be helpful to educate consumers about the environmental impact of food consumption, but it is not effective in encouraging behavioural change (Campbell-Arvai et al, 2014).…”
Section: Discussionmentioning
confidence: 75%